METHOD OF CALCULATION OF AIR-FUEL MIXTURE MINIMUM IGNITION ENERGY IN GAS ENGINE - Abramchuk, F.; Kabanov, A.; Shvydkyi, D. (Avtomobilʹnyj Transport (Harʹkov), 2013)
The improved method of minimum ignition energy calculation in a gas engine that takes into account radiation energy losses in a flame kernel has been presented. Comparison of calculation results using this model with experimental data has been performed. Minimum ignition energy calculation results for gas ICE for different values of air-fuel ratios have been presented.